Práticas de leitura(s) no ensino fundamental: fábulas e outras linguagens - Andrade, Magnólia Pacheco (2021)
The reading in the classroom has aroused the interest of many authors with wellfounded proposals that seek to improve the teaching practice of lection and the social practices of language. The study of language genres has contributed for the student to understand the different discursive modalities that permeate our daily lives. Thus, the procedures of reading should be thought out and developed in stages in order to lead the student to deal with the text, considering the functionality of the genre and its peculiarities. That said, this research aims to contribute to improving reading levels in the student's school education, as well as subsidizing the teacher's practice of working with text in the classroom. For this purpose, a Didactic Module will be built, with pedagogical activities, anchored in some texts, whose selection included the study with the fable and other languages, such as video, lyrics, informative text, the imagery, on which they will be elaborated, issues focusing on the characteristics, production and reception of these genres. The methodology used was action research, which is justified, mainly, for its collaborative character and for presenting situational characteristics, insofar as it aims to diagnose a specific problem in a specific situation, in order to achieve some practical result. As a theoretical basis, we consider the precepts postulated by Paiva (2019), Marcuschi (2002), Cândido (2004), Dezotti (2018), Kleiman (2005), Koch (2018) and Rojo (2009), among others. With the development of this research, we intend to promote reading as a social practice. For this, we use pedagogical, written and audiovisual resources, exploring the various semiosis present in the texts, in order that the proposed activities are attractive, pleasant and effective in the teaching-learning process.